2009
DOI: 10.1051/medsci/200925169
|View full text |Cite
|
Sign up to set email alerts
|

Anémie de Diamond-Blackfan

Abstract: Biogenèse des ribosomes et érythropoïèse : un lien inattenduLa biogenèse des ribosomes est l'activité métabolique la plus consommatrice d'énergie dans une cellule qui prolifère. La synthèse des 4 ARN et des 79 protéines ribosomiques qui composent les deux sous-unités ribosomiques mobilise l'essentiel de l'activité transcriptionnelle, les ARN messagers (ARNm) codant les protéines ribosomiques comptant pour la moitié des ARNm cellulaires. Par ailleurs, la production des ribosomes est étroitement connectée à la r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The SSU processome is composed of pre-rRNA, small nucleolar RNAs and more than 70 different associated proteins. Dysfunction of ribosome biogenesis is associated with human diseases, including Diamond–Blackfan anemia (DBA), 5q minus (del (5q − )) syndrome, dyskeratosis congenita and Bowen-Conradi syndrome 12 , 13 , 14 . In addition to carrying genetic mutations affecting ribosome biogenesis, these human diseases share same clinical features, and are thus termed as “ribosomopathies” 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The SSU processome is composed of pre-rRNA, small nucleolar RNAs and more than 70 different associated proteins. Dysfunction of ribosome biogenesis is associated with human diseases, including Diamond–Blackfan anemia (DBA), 5q minus (del (5q − )) syndrome, dyskeratosis congenita and Bowen-Conradi syndrome 12 , 13 , 14 . In addition to carrying genetic mutations affecting ribosome biogenesis, these human diseases share same clinical features, and are thus termed as “ribosomopathies” 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of rRNA synthesis and subsequent nucleolar stress may lead to severe anemia in humans (Aguissa-Toure et al, 2009;Narla and Ebert, 2010) and zebrafish (Bielczyk-Maczynska et al, 2015;Danilova et al, 2008). Previous studies showed that mutations in ERCC2/XPD resulted in beta-thalassemia in patients with trichothiodystrophy (Tolmie et al, 1994;Viprakasit et al, 2001).…”
Section: Ercc2/xpd Deficiency Results In Hematopoiesis Defectsmentioning
confidence: 99%
“…Consistent with this hypothesis, rRNA synthesis was disturbed in ercc2/xpd mutants. Severe anemia, e.g., Diamond-Blackfan anemia and Shwachman-Diamond syndrome (Aguissa-Toure et al, 2009;Narla and Ebert, 2010), is a typical feature of human ribosomopathies. Hematopoiesis in ercc2/xpd mutants was impaired, and most downstream hematopoietic lineages were dramatically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RPS24 deficiency leads to an impairment in the ETS (external transcribed spacer) of 18S rRNA (52), RPS10 and RPS26 deficiency to an accumulation of the 18S-E rRNA (45). Thus, different RP gene mutations either from the small or the large ribosome subunits lead to different rRNA defects but as a phenotypic result to the same erythroid precursor defect, in association or without congenital abnormalities (Figure 2) (53). …”
Section: Dba As the First Ribosomopathymentioning
confidence: 99%